Cryptococcal meningoencephalitis: time for action. Issue 9 (September 2021) - Stott, Katharine Elizabeth; Loyse, Angela; Jarvis, Joe N; Alufandika, Melanie; Harrison, Thomas Stephen; Mwandumba, Henry C; Day, Jeremy N; Lalloo, David G; Bicanic, Tihana; Perfect, John R; Hope, William
Summary: Cryptococcal meningoencephalitis was first described over a century ago. This fungal infection is preventable and treatable yet continues to be associated with excessive morbidity and mortality. The largest burden of disease resides in people living with HIV in low-income and middle-income countries. In this group, mortality with the best antifungal induction regimen (7 days of amphotericin B deoxycholate [1·0 mg/kg per day] and flucytosine [100·0 mg/kg per day]) in a clinical trial setting was 24% at 10 weeks. The world is now at an inflection point in terms of recognition, research, and action to address the burden of morbidity and mortality from cryptococcal meningoencephalitis. However, the scope of interventional programmes needs to increase, with particular attention to implementation science that is specific to individual countries. This Review summarises causes of excessive mortality, interventions with proven survival benefit, and gaps in knowledge and practice that contribute to the ongoing high death toll from cryptococcal meningoencephalitis. Translations: For the Vietnamese and Chichewa translations of the abstract see Supplementary Materials section.